2022
DOI: 10.1186/s12974-022-02666-w
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 deficiency decreases alcohol intake controlling anxiety-like behavior via modification of glutamatergic transmission in corticostriatal circuits

Abstract: Background Alcohol use disorders result from repeated binge and chronic alcohol consumption followed by negative effects, such as anxiety, upon cessation. This process is associated with the activation of NLRP3 inflammasome-mediated responses. However, whether and how inhibition of the NLRP3 inflammasome alters alcohol intake and anxiety behavior remains unclear. Methods A combination of drinking-in-the-dark and gavage was established in NLRP3-knoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Similarly, immune factors that are recruited during alcohol dependence (e.g., TNF-α, IL-6, BDNF, etc.) have been shown to modulate inhibitory and excitatory synaptic transmission via the modulation of neurotransmitter release and receptors ( Roberts et al, 2019 ; Li et al, 2022 ; Peregud et al, 2023 ; Coleman and Crews, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, immune factors that are recruited during alcohol dependence (e.g., TNF-α, IL-6, BDNF, etc.) have been shown to modulate inhibitory and excitatory synaptic transmission via the modulation of neurotransmitter release and receptors ( Roberts et al, 2019 ; Li et al, 2022 ; Peregud et al, 2023 ; Coleman and Crews, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol addiction serves as a foundational element in the development of ALD, and NLRP3 appears to play a role in this context as well. Indeed, a study conducted by Li et al demonstrated that NLRP3-knockout mice exhibit reduced binge alcohol intake and diminished anxiety-like behaviors during alcohol withdrawal compared to those observed in the control mice [59]. Other in vivo studies explored the effects of the IL-1 receptor antagonists in caspase-1, ASC, or type I IL-1β receptor-(IL-1R1) deficient mice, underlining the importance of IL-1β, a product of the NLRP3 inflammasome, in the onset of the inflammation of ALDs [60].…”
Section: Alcohol-related Liver Diseases (Alds)mentioning
confidence: 99%
“…Research on depression in various brain regions has been conducted. Notably, the medial prefrontal cortex (MPFC) of rats subjected to chronic social defeat stress (CSDS) exhibits substantial alterations [20], and inflammation or injury in the striatum also influences depressive symptoms [21,22]. Moreover, the nucleus accumbens [23] and the hippocampus [24,25] play crucial roles in depressive behavior.…”
Section: Introductionmentioning
confidence: 99%